(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
This study explores the impact of body image discrepancy and self-esteem on Abnormal eating attitudes among undergraduates. It was a cross-sectional study with descriptive study design, a multistage sampling technique was used to collect data from 247 students. The mean age of respondents was 20.04 ± 2.6 years, with a predominance of females (79.8%). Among participants, 26.3% reported dissatisfaction with their body image, 18.0% had low self-esteem, and 28% were predisposed to abnormal eating attitudes. A significantly higher proportion of participants dissatisfied with their body image (90.2%) exhibited unhealthy eating attitudes compared to 36.1% of those satisfied with their body image, a difference that was statistically significant (p < 0.001). Additionally, 53.4% of students with eating disorders had low self-esteem, while 32.9% and 13.7% exhibited average and high self-esteem, respectively. However, this relationship between self-esteem levels and eating disorders was not statistically significant (p = 0.679). The findings reveal a strong association between body image dissatisfaction and abnormal eating attitudes, highlighting body image as a critical factor in predicting unhealthy eating behaviors among students. However, self-esteem showed no statistically significant relationship with abnormal eating attitudes. These findings underscore the need for targeted interventions addressing body image concerns to promote healthier eating behaviors among undergraduates.